2019
DOI: 10.1002/jcb.29457
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor enhances tendon‐bone healing by activating Yes‐associated protein for angiogenesis induction and rotator cuff reconstruction in rats

Abstract: Local angiogenesis following rotator cuff reconstruction is crucial for tendon-bone healing. The current research on the mechanism underlying angiogenesis that promotes tendon-bone healing is scarce. This study investigates the mechanism underlying vascular endothelial growth factor (VEGF)-Hippo signaling pathway's involvement in tendon-bone healing following rotator cuff reconstruction.Verteporfin, the inhibitor of the Yes-associated protein (YAP), was used to mechanically test and analyze two groups of tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…[6][7][8] Previous studies have discovered that YAP exerts important effects in the regulation of cellular senescence, in addition to cell proliferation and apoptosis, but the effects vary with different cells. [9][10][11][12] Additionally, YAP is found widely implicated in vascular physiopathology processes, 13,23 such as modulating the activation of endothelial cellular and vascular inflammation, the hallmark of senescence. 14,15 Recently, it has been found that YAP could activate the mammalian target of rapamycin (mTOR), a critical regulator of regulating life span and ageing.…”
mentioning
confidence: 99%
“…[6][7][8] Previous studies have discovered that YAP exerts important effects in the regulation of cellular senescence, in addition to cell proliferation and apoptosis, but the effects vary with different cells. [9][10][11][12] Additionally, YAP is found widely implicated in vascular physiopathology processes, 13,23 such as modulating the activation of endothelial cellular and vascular inflammation, the hallmark of senescence. 14,15 Recently, it has been found that YAP could activate the mammalian target of rapamycin (mTOR), a critical regulator of regulating life span and ageing.…”
mentioning
confidence: 99%
“…Atypical Cadherin plays an essential role in the process of biological development and tissue morphogenesis. FAT is the first transmembrane receptor identified to affect the expression of the Hippo pathway, and it is also a transmembrane apex determinant 35 .…”
Section: The Upstream Regulatory Network Of the Hippo Signaling Pathwaymentioning
confidence: 99%
“…The crosstalk mechanism between insulin and insulin like growth factor 1 (IGF-1) signaling pathway in pancreatic cancer inhibits the expression of phosphatidylinositol 3-kinase (PI3K) explicitly, effectively reducing YAP/TAZ 44 . In addition, vascular endothelial growth factor (VEGF) could activate VEGF receptors and inhibit the phosphorylation of LATS1/2 and YAP 35 .…”
Section: The Upstream Regulatory Network Of the Hippo Signaling Pathwaymentioning
confidence: 99%
“…After the tendon injury, it often leads to limb dysfunction, severe cases, or even disability without repairation in time (Ando et al, 2019). Tendon-bone healing is an important factor in determining the success of ligament reconstruction (Li et al, 2019;Huang et al, 2020). Whether it is knee cruciate ligament, lateral collateral ligament, posterolateral complex reconstruction, shoulder joint sleeve repair, or ankle ligament reconstruction, the degree of tendonbone healing directly affects the postoperative rehabilitation process and surgical effect (Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on improving tendon-bone healing have mainly focused on promoting ligament-bone integration at tendon sites (Xu et al, 2019). This includes the use of periosteum, biogels, scaffolds, growth factors, stem cells, or other reconstruction materials that promote bone growth or ligament attachment points (Uz et al, 2019;Huang et al, 2020;Rodriguez-Vazquez and Ramos-Zuniga, 2020;Sadeghinia et al, 2020). However, reviews describing the application of tissue engineering scaffold, especially biomaterials, in tendonbone healing in vivo are lacking.…”
Section: Introductionmentioning
confidence: 99%